Effect of Rhizome Type to Viability, Growth, and Productivity of Three Turmeric Varieties - Nur Laela Wahyuni Meilawati; NFN Melati; Devi Rusmin (Pusat Penelitian dan Pengembangan Perkebunan, 2018)
Turmeric development to fulfil market demand as raw material for herbal industry requires qualified planting material in adequate quantities. This study aimed to evaluate the effect of varieties and seeds type of turmeric to the seeds efficiency, seeds viability, plant performance and rhizome yield. This experiment was conducted at the greenhouse of Indonesian Spices and Medicinal Crops Research Institute (ISMCRI), Bogor and Cicurug Research Installation, Sukabumi from November 2016 to July 2017. The study was arranged in split plot with 3 replications. The main plot was three varieties of turmeric: Curdonia, Turina 2 and Turina 3. The subplot was eight types of seeds-rhizome: (a) single finger rhizome, (b) finger rhizome with one branch, (c) finger rhizome with >1 branches, (d) mother rhizome split 2 horizontally, (e) mother rhizome split 2 vertically, (f) mother rhizome split 4 horizontally, (g) mother rhizome split 4 vertically and (h) whole mother rhizome. Parameters measured were seeds viability, growth and rhizomes yield. Seeds efficiency of Curdonia and Turina 2 can be achieved by using finger rhizome of about 0.49 t.ha-1 for both varieties, rhizome yields of 6.63 t.ha-1 and 11.45 t.ha-1 respectively. Another alternative were the use of 0.47 t.ha-1 mother rhizome split 4 vertically, yielding 9.65 t.ha-1 and 14.20 t.ha-1 fresh rhizome for Curdonia and Turina 2 varieties, consecutively. However, for Turina 3 variety, the seeds efficiency was shown by using mother rhizome split 4 horizontally of 0.66 t.ha1 and yielding fresh rhizome of 17.44 t.ha-1.